Sala Odeon: contribuições para a História do Cinema na Amazônia: a recepção e a exibição cinematográficas no início do século XX - MELO, Ana Claudia da Cruz (Universidade Federal do Tocantins, 2023)
In this article, we present the results of the research that focused on the history of the Odeon amusement room, built in Belém do Pará, Brazil, at the beginning of the 20th century. In the light of reception studies, the research aimed to raise elements that allowed inferences about the profile of the public and the nature of the films exhibited during the 1910s, in the context of an Amazon city, which was experiencing economic and migratory impacts of the First Cycle of Rubber Exploitation (1850 to 1920). For the operationalization of the methodology of the studies, we visited the memories of the pioneer of Spanish cinema, Ramón de Baños Martínez, about his period in the capital of Pará, hired as a projectionist, camera operator and photographer. We also sought to gather information about Odeon's programming, in the pages of the newspaper O Estado do Pará, a periodical founded in 1911. Theoretical-methodological movement guided by Bernardet and Mascarello, regarding the need for research on the History of Brazilian Cinema to go beyond the field of film production. The investigation revealed, among other aspects, that even given the predominance of showing imported, European and North American films, the public was always eager for national and, above all, local productions, applauded after facing long lines and in late-night sessions. It also reveals the colossal audiences of pornographic films, exclusively for male audiences, sold as a miraculous elixir for the problems of sexuality.